The Influence of Online Learning Media on Students’ Learning Outcomes - Anggaira, Aria Septi (Attractive : Innovative Education Journal, 2022)
The purpose of this study was to determine the influence of online-based learning media (padlet) on teaching media courses. This research is experimental research using a form of quasi-experimental design. The research was conducted on students of the English Study Program IAIN Metro. Samples were taken by Cluster Random Sampling technique with a sample of 24 students The research was conducted online through Zoom meetings and online quizzes. Data collection techniques by giving Pretest and Posttest using t-test. The results of the study can be concluded that the learning outcomes of students who apply padlet learning media are higher than the learning outcomes of students who apply direct learning models. This means that there is an influence on the use of padlet learning media on student learning outcomes. The use of game-based learning-based technology can be put to good use for learning needs. Keywords: Learning Media, Online, Padlet, Learning Outcomes